2014
DOI: 10.1186/1746-6148-10-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and anti-nociceptive effects of prolonged lidocaine, ketamine, and butorphanol infusions alone and in combination in healthy horses

Abstract: BackgroundProlonged drug infusions are used to treat horses with severe signs of pain, but can be associated with altered gastrointestinal transit. The purpose of this study was to determine the effects of prolonged constant rate infusions (CRI) of lidocaine (L), butorphanol (B), and ketamine (K) alone and in combination on gastrointestinal transit, behavior, and thermal nociceptive threshold in healthy horses.MethodsEight healthy adult horses were used in a randomized, cross-over, blinded, prospective experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
9
2
1
Order By: Relevance
“…Excepting for the brief report by Steffey and Pascoe [7] there are no published studies describing the effects of meperidine on nociception in horses. However, using a model similar to that described for the currently reported study similar observations on thermal nociception have been reported following administration of a constant rate infusion of butorphanol [30] and IV administration of methadone to horses. Although, 1 mg/kg has been previously reported to be a clinically acceptable dose, there are only minimal data to support this [31].…”
Section: Discussionsupporting
confidence: 58%
“…Excepting for the brief report by Steffey and Pascoe [7] there are no published studies describing the effects of meperidine on nociception in horses. However, using a model similar to that described for the currently reported study similar observations on thermal nociception have been reported following administration of a constant rate infusion of butorphanol [30] and IV administration of methadone to horses. Although, 1 mg/kg has been previously reported to be a clinically acceptable dose, there are only minimal data to support this [31].…”
Section: Discussionsupporting
confidence: 58%
“…Ketamine infusion (1.2 mg/kg bwt/h for up to 96 h) was associated with a significant delay in total gastrointestinal transit time in one report . In another study, constant‐rate infusion administration of lidocaine plus butorphanol or lidocaine plus butorphanol and ketamine resulted in delayed total gastrointestinal transit time and decreased faecal output, whereas each drug given individually and all other combinations of the 3 drugs did not delay transit, relative to placebo, in healthy horses . Thus, while multimodal therapy may be necessary in horses with severe pain, one should carefully monitor faecal output and reduce or change the drugs administered on a case‐by‐case basis.…”
Section: Potential Adverse Effects Of Analgesic Therapy and Strategiementioning
confidence: 99%
“…Systemically administered lidocaine has been found to have anti-inflammatory properties such as reduction of mucosal cyclooxygenase-2 expression and neutrophil count in ischemic-injured equine intestine or amelioration of the negative effects of flunixin meglumine on the recovery of injured mucosa [ 20 ]. It has been observed that there were no effects of prolonged lidocaine (continuous rate) infusion on gastrointestinal transit, except when in combination with butorphanol [ 21 ].…”
Section: Introductionmentioning
confidence: 99%